Dono ed economie altre: per un nuovo contratto sociale - Antonietta Di Vito (EtnoAntropologia)
The article focuses on the recent debate, about gift and the non-market economies, born especially around the new lecture of classical texts of Marcel Mauss and Karl Polanyi. The article is meant to show that the renewed interest is rooted in the contemporary crisis of relationships, of social ties, and in the effects of commodification of the utilitarian market economies. The theme of the gift is a narrative and theorethical tool to rethinking about the exchange and the social relationships throughout, both from the affective and private point of view than economical and collective too.